2018
DOI: 10.1111/gfs.12393
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in feed intake, diet digestibility and diet composition by lactating and non‐lactating goats browsing in a semi‐arid rangeland of Argentina

Abstract: We determined the seasonal nutrient and secondary compound intake, in vivo diet digestibility (DD) and diet species composition of goats in different physiological states in a desert rangeland of Argentina. During the wet and the dry seasons, 24 mature female Creole goats (six non‐lactating, non‐pregnant and six lactating in each season) were used in a 2 × 2 factorial design. Diet botanical composition, DD and dry‐matter intake (DMI) were estimated by the combined use of visual observation, microhistological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
(90 reference statements)
2
9
0
Order By: Relevance
“…Seasonality creates pulses in forage quality and availability (Duncan, Reid, Thoss, & Elston, 2005; Egea et al., 2019) and affects distribution of surface water as well as the physiological urge to drink (Chamaillé‐Jammes, Mtare, Makuwe, & Fritz, 2013b; Wato et al., 2018). Generally, there are more forage resources and greater availability of water during the wet season than during the dry season.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonality creates pulses in forage quality and availability (Duncan, Reid, Thoss, & Elston, 2005; Egea et al., 2019) and affects distribution of surface water as well as the physiological urge to drink (Chamaillé‐Jammes, Mtare, Makuwe, & Fritz, 2013b; Wato et al., 2018). Generally, there are more forage resources and greater availability of water during the wet season than during the dry season.…”
Section: Introductionmentioning
confidence: 99%
“…Time spent grazing was similar among animal types, which may relate to a likely increase in heat energy associated with longer grazing time and little or no association between rate of biting and energy expenditure [15–17]. Some findings of Manousidis et al [18] with adult Greek goats grazing Mediterranean woody rangeland over a 2-year period are similar to those of Egea et al [14]. An analysis was conducted to determine chemical characteristics responsible for the selection of specific plants and plant groups and influence of animal physiological stage.…”
Section: Production Systemmentioning
confidence: 65%
“…Moreover, the physiological state of the animal, as impacting nutrient and energy needs, can influence selectivity and diet composition. As an example, with Creole goats in a woodland area of the central Monte Desert in Argentina, Egea et al [14] observed not only greater dry matter (DM) intake by goats in early lactation compared with nonlactating animals but also relatively more consumption of high-protein and tanniferous shrubs. The latter findings presumably relate to the greater protein requirement of goats when lactating than dry and tannin binding of protein in the rumen to increase intestinal amino acid absorption.…”
Section: Production Systemmentioning
confidence: 99%
“…2 Contact between animals is the time spent by the animals seeking the stimulus animal. 3 Latency to contact is the time taken to make contact with either the own or alien animal at the end of the test area. 4 Low bleats refer to the quiet vocalizations produced with the mouth closed.…”
Section: Apromentioning
confidence: 99%
“…In most rangelands worldwide, especially under arid and semiarid conditions, both the energy and protein consumption is found to be below the animal's requirements because the poorest quality forages are available, especially during the dry season [1][2][3]. This situation is particularly critical during the last third of pregnancy.…”
Section: Introductionmentioning
confidence: 99%